Habitability of the universe before earth - Gordon, Richard 1943-; Sharov, Alexei A. (Astrobiology : exploring life on earth and beyond, 2018)
Habitability of the Universe before Earth: Astrobiology: Exploring Life on Earth and Beyond (series) examines the times and places—before life existed on Earth—that might have provided suitable environments for life to occur, addressing the question: Is life on Earth de novo, or derived from previous life? The universe changed considerably during the vast epoch between the Big Bang 13.8 billion years ago and the first evidence of life on Earth 4.3 billion years ago, providing significant time and space to contemplate where, when and under what circumstances life might have arisen. No other book covers this cosmic time period from the point of view of its potential for life. The series covers a broad range of topics encompassing laboratory and field research into the origins and evolution of life on Earth, life in extreme environments and the search for habitable environments in our solar system and beyond, including exoplanets, exomoons and astronomical biosignatures.--Provided by publisher.